The dark side of the boom: dutch disease, competition with China, and technological upgrading in colombian manufacturing - Branstetter, Lee G. (2024)
The natural resource boom of the 2000s spurred growth in income and consumption in many commodity-exporting nations. However, this paper brings together a previously unused combination of data sets from Colombia to document evidence of a downside – the currency appreciation associated with this boom led to a significant and persistent decline in R&D spending and in investment in technological upgrading by Colombian manufacturing firms. Our empirical strategy exploits differences in firms' sales across products and export destinations to create firm-specific measures of exposure to exchange rate shocks both abroad and at home. We link these new measurements of exchange rate exposure with Colombian micro data on R&D investment and technology upgrading. The key finding is that real exchange rate appreciation drives significant reductions in both firm-level R&D investment and a measure of technology upgrading that includes expenditure on capital goods, technology licensing, worker training, and other expenditures related to the adoption of new technology. Even after key commodity prices dropped significantly in the mid-2010s, inducing a substantial and long-lasting Colombian currency depreciation, investments in R&D and technology upgrading remained at subdued levels. Our estimated effects suggest that the resource boom and associated appreciation had a significant and persistent negative effect on technological development of Colombian manufacturing firm, and these conclusions remain even after careful attempts to simultaneously control for rising competition with Chinese manufacturers, which also had a negative effect on Colombian firms' technology investments, and the effects of trade liberalization at home and abroad. Similarities between Colombia and other commodity-exporters suggest that the effects documented in this paper may be widespread.